Heuristic Method for Photo-detectors Localization over Continuous Crystal Scintillation Cameras - Rodríguez Colmeiro, Ramiro G. (2018)
The construction process of large scintillation cameras with continuous crystals is a complex problem affected by multiple variables, from the physical construction of the scintillation crystal to the dispersion in the sensibility of photomultiplier tubes. The selection of these variables have a strong impact on the final performance of the scintillation camera. A new method to select photomultiplier is presented in this paper, regarding its gain, making use of k-means clustering and genetic algorithms. The proposed algorithm was tested and applied in the construction of six scintillation cameras for the Argentinean positron emission tomogaph prototype (AR-PET), a problem with more than 10+600 possible configurations. The resulting configuration of the scintillation cameras reduced the software-freecalibration FWHM of the camera from 20% to 15% average.